On Invariance Weakness in the KSAm Algorithm. (2015) - Crainicu, Bogdan
Abstract: In this paper, we analyze the effect of the invariance weakness defined by Fluhrer, Mantin and Shamir in [8] on the a new variant of RC 4 Key-Scheduling Algorithm, called KSAm, proposed by Crainicu and Boian in [2]. We demonstrate that the state permutation S of the RC 4 with KSAm after running the new Scrambling_ 1 component introduced by KSAm is not b-conserving, which means that KSAm does not expose the invariance weakness, being therefore capable to strengthen the overall RC 4 stream cipher. We also propose an algorithmic approach model for the identification of the mappings of the secret key bits to identifiable patterns in the initial permutation S . The propsed model is suitable for testing any Scrambling- like mechanism applied to a permutation, where the values of two entries are swapped at each step.